2014
DOI: 10.1080/09540121.2014.906558
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of antiretroviral therapy use among alcohol drinkers at HIV clinics in Tshwane, South Africa

Abstract: Alcohol use is associated with compromised antiretroviral therapy (ART) adherence. We aimed to identify patterns and predictors of ART use among alcohol drinkers. Using purposive sampling, we recruited 304 male and female patients from two ART clinics in Tshwane, South Africa. Interviews were conducted using a structured questionnaire comprising measures of demographic factors, psychosocial factors (i.e., ART adherence, self-efficacy beliefs, alcohol and ART interactions beliefs, ART-alcohol outcome expectancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 11 publications
4
22
0
Order By: Relevance
“…Six investigations found that stigma was significantly associated with poor self-reported adherence at the multivariate level, after adjusting for factors such as demographics, perceived health, structural barriers, and alcohol and drug use [42,44,45,47,49,56]. Two prospective investigations lent support to this association as well.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 73%
See 2 more Smart Citations
“…Six investigations found that stigma was significantly associated with poor self-reported adherence at the multivariate level, after adjusting for factors such as demographics, perceived health, structural barriers, and alcohol and drug use [42,44,45,47,49,56]. Two prospective investigations lent support to this association as well.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 73%
“…These instruments are characterized by a range of subconstructs, including internalized (e.g., negative self-perception), anticipated (e.g., renegotiating social relationships), and enacted (e.g., healthcare discrimination) stigmas. A combination of enacted and anticipated stigma items was used for two studies [44,45], but the exact stigma measure used was not mentioned.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…Indications of the benefit of greater self-efficacy among individuals with HIV have been found in studies showing positive associations between medication adherence self-efficacy and medication adherence (Parsons et al, 2008; Kekwaletswe and Morojele, 2014), and between smoking cessation self-efficacy and successful smoking cessation in HIV-infected populations (Shuter et al, 2014). Notably, another study demonstrated an association between lower self-efficacy to resist drinking and higher levels of drinking among HIV-infected youths (Naar-King et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, binge drinking rather than the cumulative exposure of hazardous drinkers was predictive of non-adherence to ART [7]. A recent study conducted in HIV clinics in Tshwane, Gauteng province in South Africa, found a significant association between level of alcohol use and degree of non-adherence [27]. …”
Section: Introductionmentioning
confidence: 99%